2019
DOI: 10.1001/jamaoncol.2019.2572
|View full text |Cite|
|
Sign up to set email alerts
|

Efficacy and Long-term Peripheral Sensory Neuropathy of 3 vs 6 Months of Oxaliplatin-Based Adjuvant Chemotherapy for Colon Cancer

Abstract: IMPORTANCE Oxaliplatin-based chemotherapy is associated with debilitating peripheral sensory neuropathy (PSN) for patients with stage III colon cancer. OBJECTIVE To assess disease-free survival (DFS) and long-lasting PSN in patients treated with 3 vs 6 months of adjuvant oxaliplatin-based chemotherapy. DESIGN, SETTING, AND PARTICIPANTS An open-label, multicenter, phase 3 randomized clinical trial of 1313 Asian patients with stage III colon cancer was conducted investigating the noninferiority of 3 vs 6 months … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
92
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(96 citation statements)
references
References 27 publications
2
92
2
Order By: Relevance
“…Moreover, a previous report indicated that peripheral sensory neuropathy lasts for a long period and affects QOL after treatment. 47 Thus, physicians should consider QOL during not only the rst-line treatment but also the overall survival time when selecting the regimens.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, a previous report indicated that peripheral sensory neuropathy lasts for a long period and affects QOL after treatment. 47 Thus, physicians should consider QOL during not only the rst-line treatment but also the overall survival time when selecting the regimens.…”
Section: Discussionmentioning
confidence: 99%
“…46 In the ACHIEVE trial, at a median follow-up of 3 years, the prevalence all grade neuropathy was 23.3% vs 10%, while grade 3 was only 0.3 vs 0%. 47 In the ACHIEVE trial, it was also observed that the incidence of any grade PSN was lower for patients treated with CAPOX compared with FOLFOX in both the 6 months and 3 months treatment groups. All other studies did NR any LT.…”
Section: Fluoropyrimidines With Oxaliplatin Combinationsmentioning
confidence: 97%
“…The 3 months treatment arm received a grade B based on non-inferiority in combination with less toxicity. [46][47][48] T4 versus T1-3 and N2 versus N1 subgroups were prespecified however their combinations in subgroups and its interaction test was not significant, thus these subgroup analyses were post hoc and could not be graded.…”
Section: Fluoropyrimidines With Oxaliplatin Combinationsmentioning
confidence: 99%
“…But patients with diabetes seem to develop neuropathy at lower cumulative dose [26]. Another report suggests that incidence neuropathy may be less XELOX 3-wekely (130 mg/m 2 ) regimen than FOLFOX 2-weekly (85 mg/m 2 ) regimen [27]. Therefore, choice of oxaliplatin in the adjuvant treatment of colon cancer should be based on individual assessment of risk of recurrence and other clinical factors.…”
Section: Stage III Colon Cancermentioning
confidence: 99%